(untitled) (Pedagogy of Higher and Secondary Education, 2012)
Pastukhova L. V. Theoretical foundations of the Dalton plan. The article is devoted to the description of the Dalton plan pedagogical model in the Ukrainian and foreign scientific pedagogical literature. The Dalton Plan theory is analyzed.